Questions kids ask about mammals - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Answers various questions kids ask about mammals such as, do bears sleep through winter?; why are giraffes so tall?; what do bats eat?; why don't gorillas climb trees?; what is a gnu?; what is the fastest land animal?